Desperation in death - Robb, J. D., 1950- (New York : St. Martin's Press, 2022)
In New York City, 2061, the Pleasure Academy abducts young girls and trains them for a life of sex slavery. Thirteen-year-old Dorian escapes and Dallas tries to expose a sex trafficking ring.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Women detectives -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Abduction -- Fiction; Human trafficking -- Fiction; Exploitation -- Fiction; Good and evil -- Fiction; Girls -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; New York (N.Y.) -- Fiction; Detective and mystery fiction; Romance fiction; Thrillers (Fiction)